2008
DOI: 10.1071/ea08049
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of methanogens in ruminants in Queensland

Abstract: Abstract. Methane emissions from ruminant livestock represent a loss of carbon during feed conversion, which has implications for both animal productivity and the environment because this gas is considered to be one of the more potent forms of greenhouses gases contributing to global warming. Many strategies to reduce emissions are targeting the methanogens that inhabit the rumen, but such an approach can only be successful if it targets all the major groups of ruminant methanogens. Therefore, a thorough knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
4
18
0
Order By: Relevance
“…The most predominant species of methanogens in the three groups were related to the genus Methanobrevibacter. This is in agreement with Pei, Mao, Cheng and Zhu previous studies indicating species belonging to the genus Methanobrevibacter as the major methanogens in the rumen of sheep (Wright et al, 2004 andSkillman et al, 2004;Nicholson et al, 2007) and cattle (Whitford et al, 2001;Skillman et al, 2006;Nicholson et al, 2007;Ouwerkerk et al, 2008), of which some were associated with the rumen protozoa (Tokura et al, 1999a;Sharp et al, 1998;Chargan and Ushida, 2004). The predominance of this genus has also been suggested before based on cultivation studies (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…The most predominant species of methanogens in the three groups were related to the genus Methanobrevibacter. This is in agreement with Pei, Mao, Cheng and Zhu previous studies indicating species belonging to the genus Methanobrevibacter as the major methanogens in the rumen of sheep (Wright et al, 2004 andSkillman et al, 2004;Nicholson et al, 2007) and cattle (Whitford et al, 2001;Skillman et al, 2006;Nicholson et al, 2007;Ouwerkerk et al, 2008), of which some were associated with the rumen protozoa (Tokura et al, 1999a;Sharp et al, 1998;Chargan and Ushida, 2004). The predominance of this genus has also been suggested before based on cultivation studies (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…The primer 344F also contained a 38 nt G:C 'clamp (Vetriani et al, 1999) for DGGE analyses. Of the original 17 samples only 14 yielded PCR products, which were subjected to DGGE using the Bio-Rad D-code System (Bio-Rad, Hercules, CA, USA; Ouwerkerk et al, 2008) and the gel images were captured using a Typhoon scanner and Typhoon TRIO Variable Mode Imager (GE Healthcare Life Sciences, Parramatta, NSW, Australia).…”
Section: Animal Sampling Protocol and Digesta Preservationmentioning
confidence: 99%
“…However, in general, 896 reductive acetogens are not competitive against methanogens as H2 partial pressure is usually below 897 the threshold required (Morgavi et al 2010). Efforts to boost their numbers and activity to compete 898 with methanogenesis in vitro or in vivo have not been successful (Demeyer et al 1996; Le Van et alenvironments such as the macropod (Ouwerkerk et al 2008) might yield strategies that make 901 reductive acetogenesis more favourable in the rumen. 902…”
Section: Forage Quality and Methane Production 707mentioning
confidence: 99%
“…However, for Archaea it has been shown thatincrease of methyl compounds associated with methylamines, as well as methanol would be 3676 expected to increase during wet season months. In a previous study of methanogenic archaea 3677 associated with different forage quality (Ouwerkerk et al 2008), no members of the RCC were 3678 observed in this study of cattle consuming, Pangola grass, Leucaena, Ryegrass and Speargrass 3679 conserved forages ranging from 20 to 200 g CP/ kg DM, and potentially the DGGE and clone 3680 library techniques used were insensitive to RCC methanogens. 3681…”
mentioning
confidence: 99%